2016
DOI: 10.1055/s-0042-117631
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of pre-procedure simethicone and N-acetylcysteine to improve mucosal visibility during gastroscopy – NICEVIS

Abstract: Background and study aims: Mucosal views can be impaired by residual bubbles and mucus during gastroscopy. This study aimed to determine whether a pre-gastroscopy drink containing simethicone and N-acetylcysteine improves mucosal visualisation. Patients and methods: We conducted a randomized controlled trial recruiting 126 subjects undergoing routine gastroscopy. Subjects were randomized 1:1:1 to receive: A—pre-procedure drink of water, simethicone and N-acetylcysteine (NAC); B—water alone; or C—no preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…The resulting evidence form this meta-analysis is in concordance with previously published several studies (15,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) and at least two systematic reviews (38,39). First systematic review (38) was published in 2011 but has limitations of analysing trials investigating the role of Simethicone ± NAC in OGD, colonoscopy and capsule endoscopy.…”
Section: Agreement and Disagreement With Other Published Evidencesupporting
confidence: 89%
See 1 more Smart Citation
“…The resulting evidence form this meta-analysis is in concordance with previously published several studies (15,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) and at least two systematic reviews (38,39). First systematic review (38) was published in 2011 but has limitations of analysing trials investigating the role of Simethicone ± NAC in OGD, colonoscopy and capsule endoscopy.…”
Section: Agreement and Disagreement With Other Published Evidencesupporting
confidence: 89%
“…A total of 171 studies were identified from Scopus, Medline and other electronic databases. Among them, 7 RCTs (n=1,099), published until March 2018, were eligible for inclusion (28)(29)(30)(31)(32)(33)(34)(35)(36); and the reasons for ineligibility are described in PRISMA flow chart Figure 1. The extracted data from the included trials is given in Tables 1 and 2.…”
Section: Characteristics Of Selected Trialsmentioning
confidence: 99%
“…Some UGI videos were obscured by adherent mucus in the proximal stomach. The use of mucolytics such as N-acetylcysteine or pronase has been shown to be of benefit in improving mucosal visibility during gastroscopy[ 37 - 39 ], although this did not translate to the only capsule endoscopy study to date[ 40 ]. Routine use of hyoscine has been advocated to improve visualisation in OGD[ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might be because of time pressures resulting in OGD being performed too rapidly, a lack of training in recognition of early malignant disease or poor tolerance of the procedure, resulting in inadequate insufflation or an abbreviated examination. The use of antifoaming agents and mucolytics may also improve mucosal visualisation and early lesion detection 17. Cheung et al showed that alarm features were significantly less likely at presentation in these patients than those identified at first OGD 18…”
Section: Discussionmentioning
confidence: 99%